The Cherokee - Craats, Rennay; Wynn, Marilyn (Philadelphia : Chelsea Clubhouse, 2004)
Recounts the history of the Cherokee and outlines their traditional ways of life, religious beliefs, celebrations, and artwork.
The people -- Cherokee homes -- Cherokee communities -- Cherokee clothing -- Cherokee food -- Tools, weapons, and defense -- Cherokee religion -- Ceremonies and celebrations -- Music and dance -- Language and storytelling -- Cherokee art -- Stickball -- Modern artist -- Studying the Cherokees' past.
8 - 9 years
Keywords: Cherokee Indians -- History; Cherokee Indians -- Social life and customs; Cherokee Indians; Indians of North America -- Southern States